IMPORTANCE OF MULTICULTURAL EDUCATION IN REDUCING STUDENT PREJUDICE - Nining Lestari; Siti Ainaya Annisa; Izzul Hukama Izzul (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
The Importance of Reducing Students' Presuppositions in Multicultural Education. Multicultural education is education that respects diversity and includes perspectives from various cultural groups regularly. An important goal of multicultural education is equal opportunities for all students with the hope of closing the academic achievement gap between students from the majority culture and students from minority groups (Bennet in Santrock, 2019). In this research, the library study research method was used. Sukardi (in Handika, 2020) explains that library study is a required activity in research, especially academic research which has the main aim of developing theoretical aspects. The research data collection technique is collecting data from journal articles, and books related to the theory. relevant as well as from several sources on the internet. Multiculturalism provides space to create an understanding of the existence of various cultural differences in society. Education in the family environment tends not to be given much attention, considering that children's education is the responsibility of the school. This view is wrong because education is an obligation for all parties, especially parents at home. Prejudice is a negative attitude towards a group that is different from one's group based on certain characteristics. Therefore, efforts made to prevent and intervene against prejudice in children or students should involve handling the environment around the child. Multicultural education can foster more positive attitudes towards members of different community groups.